The Principles of Zakat and Tax Upon the Time of Rasulullah SAW - Dian Septiandani; Abd. Shomad (Fakultas Hukum Universitas Hang Tuah, 2017)
Zakat is one of principal worship requiring every individual (mukallaf) with considerable property to spend some of the wealth for zakat under several conditions applied within. On the other hand, tax is an obligation assigned to taxpayers and should be deposited into the state based on policies applied, with no direct return as reward, for financing the national general expense. In their development, both zakat and tax had quite attention from Islamic economic thought. Nevertheless, we, at first, wanted to identify the principles of zakat and tax at the time of Rasulullah SAW. Therefore, this study referred to normative research. The primary data was collected through library/document research and the secondary one was collected through literature review by inventorying and collecting textbooks and other documents related to the studied issue.